Identifikasi dan Prevalensi Ektoparasit Protozoa Pada Udang vannamei (Litopenaeus vanamei) di Tambak Intensif Kuala Langsa - Sri Rahayuni; Beni Al Fajar; Sara Gustia Wibowo (Jurnal Kelautan dan Perikanan Indonesia, 2022)
AbstractThis has an impact on the emergence of disease-causing pathogens, one of which is protozoa ectoparasites which leads to adecrease in production. Litopenaeus vannamei sample was taken using random sampling method. The purpose of this study was to determine the type of protozoa ectoparasite in vannamei shrimp (Litopenaeus vannamei) which were senn during identification including gills, carapace, swimming legs, walking legs and tail. The results of the identification there are 6 types of protozoan ectoparasites that infect Litopenaeus vannamei found in the Kuala Langsa intensive pond, namely Vorticella, Epystylis, Zoothamnium, Trichodina , Ichthyophirius and Oodinium. The highest prevalence is Zoothamnium, which is 30%, so it falls into the general category. Measurement of physical and chemical parameters of water in intensive ponds in Kuala langsa in the form of temperature and value 28,1-30,4oC, DO 4,6-5,9, pH 6,9-7,5 and salinity with value 15 ppt.